ANALISIS TATANIAGA JERUK SIAM BANJAR (Citrus reticulata) DI DESA KARANG BUAH KECAMATAN BELAWANG KABUPATEN BARITO KUALA - M. Ilmi Hidayat; Suslinawati .; Puput Andriani (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
The purpose of this study was to determine the trading system channel, knowing the margin marketing system, the farmer's share, marketing efficiency and problems faced in marketing system Siam Banjar Orange (Citrus reticulata) in the Village Karang Buah Belawang District of Barito Kuala Regency. This study used survey method and data sources used are primary data and secondary data. Method of determination of farmers sampled using purposive sampling method and determination of trading system agencies using snowball sampling method. The result showed in the Village Karang Buah Belawang District of Barito Kuala Regency. There are five marketing system channels, the most large margin system is on the channel III orange with big size, with a margin Rp.6000/kg, the largest farmer's share is on channel system 1 measure orange Siamese large and small, with the value of the farmer's share 100%. While most marketing system efisien located on the marketing 1 system channel for sizes large and small . The constraints faced in marketing is to maintain the quality of citrus from producer to consumer.